Predictors of prescribed and unprescribed methylphenidate abuse - McMonagle, Joseph Patrick, author; Chavez, Ernest L., advisor; Beauvais, Fred, committee member; Heggestad, Eric D., committee member; Yang, Raymond L., committee member (Colorado State University. Libraries, 2005)
This study used self-report survey data from students (grades 9 through 12) from a nationally derived sample (n=17,000) to explore hypothetical predictors of Methylphenidate (MPH) abuse for youths with and without a MPH prescription history. Variables included; history of MPH prescription, general level ('style') of substance abuse, types of aggression, gender, smoking, and the interaction of MPH prescription history and smoking. 6.4% of the sample were found to have abused MPH during the last year. There were no significant age group differences for MPH abuse. Also, MPH prescription alone did not predict MPH abuse. However, multiple regression showed that after 'style', the interaction between a history of MPH prescription and smoking behaviors was the next most significant predictor. After that, smoking and physical assault on a person were also somewhat significant. A three group (prescribed/abusing, prescribed/non-abusing, and non-prescribed/abusing) discriminant analysis showed that it was possible to discriminate between the three groups using most of these predictor variables. While non-abusers were the 'most different' group, particularly in relation to their general drug use and smoking behaviors, it was also shown that the prescribed/abusing group was different from the non-prescribed/abusing group by being more likely to be male and aggressive. A discussion of the role of nicotine as a significant predictor of MPH abuse, and its particular importance for those with a history of MPH prescription was included.
Keywords: psychotherapy; developmental psychology; public health; drug abuse; studies; teenagers; clinical psychology